The Comparison of Total Fumonisin and Total Aflatoxin Levels in Biscuit and Cookie Samples in Babol City, Northern Iran - Issa Gholamour Azizi; Samaneh Rouhi (Tehran University of Medical Sciences, 2013)
Background: Fumonisins and aflatoxins are mycotoxins that are produced by Fusarium and Aspergillus genus respectively. Due to the toxicity of aflatoxin and fumonisin and its effects on human and animals' health, the purpose of this study was analysis of total fumonisin and total aflatoxin contamination in biscuit and cookie samples in Babol City, Northern Iran.Methods: Thirty biscuit (n=15) and cookie (n=15) samples were randomly collected at supermarkets in Babol City in winter 2011. Competitive ELISA was conducted for total fumonisin and total aflatoxin separately.Results: Out of 30 biscuit and cookie samples, 28 (93.4%) samples were contaminated with <2ppm of total fumonisin and 2 (6.6%) showed infection with 2-4ppm of this toxin. The highest contamination rate of total fumonisin was 2.3 ppm in biscuit samples. In addition, none of the samples was infected by > 4ppm of total fumonisin. From 30 samples, 26 (86.7%) were contaminated with <4ppb of total aflatoxin and 4 (13.3%) were positive in total aflatoxin with ≥4ppb and highest contamination rate was found 7.9 ppb in biscuit samples. Contamination rate of samples by total aflatoxin was higher than total fumonisin.Conclusion: Since biscuits and cookies are extensively used among all ages of humans, consumption of contaminated food causes different diseases in human. Therefore, determination, management, and prevention of mycotoxins according to the climatic conditions should be considered.